Contribuições do curso de educação musical a distância da UFSCar nas percepções de licenciandos-já-professores - Santos, Terence Peixoto dos (2012)
In face of the technological evolution lived by the nowadays society, which allowed the emergence of the on-line distance education (via the internet), it has occurred over the last years in Brazil a constant growth of distance teacher education, with graduation courses that rely on large part of its development being realized through on-line activities. This growth has also relied on contributions from the Ministry of Education through programs as the Brazil Open University (UAB), for example. It is considering this scenario that it was sought to explore these new environments of formation and investigate what contributions a distance formation course brings to students that already work as music teachers. Therefore, it started from the characterization and analysis of experiences and learnings that the students-alreadyteachers pointed out as significatives in the Music Education Licentiate course at a distance of UFSCar, also seeking to relate those experiences and learnings with the categories of the knowledge base for teaching (SHULMAN, 1986, 1987; MIZUKAMI, 2004). It was applied an on-line questionnaire with the students-already-teachers who consented their participation in the research, and it was sought to reach the objectives proposed by means of an inductive analysis of the answers. The research had its methodology defined based on the principles of the qualitative research, and was characterized as being of descriptive-analytical nature. The results revealed that even already possessing large experience in music teaching, the studentsalready- teachers affirmed that the distance graduation course contributed in several aspects, being possible to identify contributions to with their content knowledge, pedagogical content knowledge and general pedagogical knowledge, just as general contributions related to distance education, learning of technological resources, personal organization, incentive for research, among others. It was finalized with the certainty that the distance education presents great possibilities and a lot of potential for teacher education and for education, and that much remains to be researched and understood in this field.